EFISIENSI TEKNIS USAHA TANI KAKAO BERDASARKAN KLON SULAWESI 1&2 DAN KLON LOKAL - Rifin, Amzul; Priatna, Wahyu Budi; Asri, Dian (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
Cocoa is an important commodity that consistently contributes to the structure of the Indonesian economy. The purpose of this study isto analyze the technical efficiency of cocoa based onclones used in PolewaliMandar. This study use Data Envelopment Analysis (DEA) and Tobit Regeression. From the results,some farmers in PolewaliMandar Regency have used the superior clones of Sulawesi 1 and Sulawesi 2 and local clones as the seeds used for side grafting. Separated by 55 farmers planted with Sulawesi 1&2 clones and 54 people using local clones. Both applications have not used input as recommended, such as the use of urea fertilizer, SP-36, KCL, pesticide, manure and labor, still many farmers of respondents who have not gained the optimal results.